The Effect of Temperature and Concentration Edible Coating of Aloe Vera Gel (Aloe Vera L.) to The Shelf Life and Sensory of Tomatoes (Solanum lycopersicum L. cv Momotaro) - Tobing, Oktavianus Lumban; Mulyaningsih, Yanyan; Aziz, Ferry Abdul (Indonesian Journal of Applied Research (IJAR), 2023)
Tomatoes (Solanum lycopersicum L. cv Momotaro) with a creeping growth or indeterminate type generally grown in the highlands have high economic value. Momotaro tomatoes were classified as climacteric fruits that are easily damaged after harvest. So, it is necessary to do low-temperature treatment and edible Aloe vera gel coating to extend shelf life and sensory. This research aims to determine the effect of low-temperature storage and the concentration of aloe vera gel edible coating, which can extend the shelf life and sensory of Momotaro tomatoes. This study used a complete randomized design of the nested pattern, with treatment edible coating aloe vera gel consisting of 3 concentrations, namely control treatment (without coating), concentration coating 50%, concentration coating 100% nested in temperatures 5°C, 10°C, 15°C, and room temperature (27°C). Conclusions from results showed that the temperature treatment of 10°C and the edible coating treatment of aloe vera gel with a concentration of 50% nested at 10°C, have better results in extending the shelf life and sensory of Momotaro tomatoes to more than 30 days because the maturity level of Momotaro tomatoes has not yet reached its chemical peak. The temperature treatment and concentration of aloe vera coating positively contribute to extending the shelf life and sensory of Momotaro tomatoes.